TRANSNATIONAL MIGRATION AND ETHNIC ENTREPRENEURSHIP AMONG THE CHAM DIASPORA IN MALAYSIA - Betti Rosita Sari (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2017)
This article is concerned with the Cham diaspora in Malaysia, who maintain transnational ties to their home land of “Kampong Cham” in Cambodia. With the process of movement and resettlement, this community confronted real challenges and had to develop new ways of life in a new milieu. From traditional forms of farming and fishing, which had been their main sources of economic support in Cambodia, these people transformed their main traditional activities to develop commercially-oriented economic activities in their new settlement.This paper aimed to answer two questions, first, how migrants use patron client relationships to survive and pursue their life in Malaysia. Second, how Cham diaspora in Malaysia who take the role of ethnic entrepreneur or patron help other migrants to negotiate transnational space and therefore facilitate transnationalism. This ethnic network plays an important role in their ethnic businesses and economic survival strategy, both for the previous migrant and new comer migrants. This paper contributes to a contemporary issue of Cham diaspora in Malaysia, one of ethnic minority in Cambodia and their strategy to face globalization by establishing transnational networking. Keywords: Diaspora, Cham, transnational migration, entrepreneurship, ethnic network, Malaysia AbstrakArtikel ini berkaitan dengan diaspora Cham di Malaysia, yang mempertahankan hubungan transnasional dengan tanah asal mereka